Use of Strategic Communication in Peace-building Initiatives Within Conflict Zones in Nigeria - Ifeanyi Martins NWOKEOCHA; Promise Adaku OBI (Journal of Humanities Education Management Accounting and Transportation, 2026)
This study examined the use of strategic communication in peace-building initiatives within conflict zones, highlighting its role in fostering dialogue, mitigating violence, and promoting social cohesion. In regions affected by political, ethnic, or communal conflicts, communication strategies are pivotal in shaping perceptions, reducing misinformation, and encouraging cooperation among conflicting parties. The study investigated how government agencies, non-governmental organizations, community leaders, and media practitioners employ strategic communication tools including public service announcements, media campaigns, interpersonal messaging, and digital platforms to influence attitudes and behaviors conducive to peace. This study is based on a systematic literature review to explore strategic communication, communication, peace-building initiatives and conflict zones in Nigeria. In this case, the method is grounded in a thorough literature review, which includes academic articles including books and online resources to explore strategic communication and peace-building. The study identified crucial practices and challenges in implementing effective communication strategies. Findings indicated that well-planned messaging that is culturally sensitive, transparent, and participatory can significantly enhance trust, reduce hostility, and facilitate reconciliation processes. Challenges such as information manipulation, limited media access in remote areas, and audience skepticism are also highlighted as factors that may hinder the effectiveness of communication efforts. The study contributed to conflict resolution and communication scholarship by demonstrating how strategic communication can serve as a catalyst for sustainable peace and offers practical recommendations for designing, implementing, and evaluating communication interventions in conflict-prone environments. The study recommended that peace-building initiatives should embed strategic communication at the planning stage rather than treating it as an auxiliary activity. Communication objectives should align clearly with peace goals such as dialogue, reconciliation, and conflict prevention